2020
DOI: 10.1039/d0se00361a
|View full text |Cite
|
Sign up to set email alerts
|

Novel Ru nanoparticle catalysts for the catalytic transfer hydrogenation of biomass-derived furanic compounds

Abstract: Highly dispersed Ru nanoparticles supported on N-doped mesoporous carbon demonstrated an admirable catalytic activity in catalytic transfer hydrogenation of 5-hydroxymethylfurfural to 2,5-dimethylfuran and furfural to 2-methylfuran.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 43 publications
(68 citation statements)
references
References 86 publications
1
66
1
Order By: Relevance
“…The D‐band to the G‐band intensity ratios (I D /I G , understood via the collective areas of the band) are 1.62, 1.72, 2.31, 2.42, 2.40 and 2.38 for MC, Au‐MC‐SI, NMC, Au‐NMC‐SI, Au‐NMC‐DP and Au‐NMC‐IW, respectively. This result revealed that imperfection in the graphite‐like sheets was raised on increasing the N‐content of the catalyst as well as after Au metal loading [67,76–79] …”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…The D‐band to the G‐band intensity ratios (I D /I G , understood via the collective areas of the band) are 1.62, 1.72, 2.31, 2.42, 2.40 and 2.38 for MC, Au‐MC‐SI, NMC, Au‐NMC‐SI, Au‐NMC‐DP and Au‐NMC‐IW, respectively. This result revealed that imperfection in the graphite‐like sheets was raised on increasing the N‐content of the catalyst as well as after Au metal loading [67,76–79] …”
Section: Resultsmentioning
confidence: 91%
“…The graphitic nature of the carbon samples (MC, NMC and supported Au catalysts) was studied by Raman spectroscopy (Figure 1d). Raman spectra consists of D‐band (1335 cm −1 )and G‐band (1590 cm −1 ),which are attributesof disordered graphitic carbon materials [76–79,83,84a] . The G‐band showcases the graphitic establishment of carbon samples, while the D‐band represent defects and suggesting an insufficient crystalline assembly of the carbons [76–79,83,84a] .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations